Shame, classroom resistance, and Bion's desire not to know - Marshall Alcorn (Universidade Estadual de Campinas, 2011)
It is not uncommon for students to resist evidence or claims taught by their teachers. This paper uses affect theory from the work of Sylvan Tomkins to understand Wilfred Bion's account of the human "desire not to know." I argue that cultural experiences with shame and disgust set in place biological responses that restrict and attack possibilities for cognitive thought. Classroom experiences that appeal to requirements for "thoughtfulness" should anticipate the biological ground of resistances and seek forms of engagement that respond to resistance through emotional rather than intellectual force.